Combining Landsat and ALOS Data for Land Cover Mapping - Abdikan, Saygin; Ustuner, Mustafa; Sanli, Fusun Balik; Bilgin, Gokhan (IEEE, 2017)
In this study, L-band ALOS PALSAR radar satellite image and Landsat TM optical satellite image were used to investigate the contribution of radar satellite image to optical satellite image for land cover mapping. Dual-polarimetric data of ALOS satellite and also normalized difference vegetation index (NDVI) generated from Landsat image were used for the analysis. In addition, different classification techniques were taken into consideration and forest dominated land cover maps were produced and the results were compared. Random Forest (RF), k-Nearest Neighbors (k-NN) and Support Vector Machines (SVM) approaches were applied as image classification techniques. While the best result among the methods is DVM, the data set in which combined data arc used gives the best general accuracy result.
Keywords: Landsat; ALOS; land cover; image classification; CLASSIFICATION; AREA; Acoustics; Computer Science; Engineering; Telecommunications